(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The existing crisis that Syria facing is contributed to spread the a phenomenon of bad debts which have the fundamental effect on performance of banks,because of their loads included banks and clients defaulting,so it was necessary to research on financial stumbling ratio with in a sample in Syrian traditional private banks consisting of: International Bank for Trade and Finance, Audi Bank, Byblos Bank, Arab Bank, Bank Bemo Saudi Fransi, Bank Syria and Overseas, during the period from 2010 To 2016 to know points of strength and weakness in order to find solutions which can reduce this a phenomena and relieves its negative effects. We noticed that the reason of stumbling is backed to two types of risks one of them regular risks and another one irregular risks, that means one of them happened because of mismanagement of credit process and failed to make credit decision depending on scientific foundations, and the another one happened because of reacting of present crisis. That study concluded,it is so importance of restructuring the mechanism of granting credit, that consistent Syrian market variables and take procedures not only to hedge the risk of default, but also processing it and helping defaulting clients especially these who have stumbled as result of irregular risks which reduce losses bank and help it collecting loans. ساهمت الأزمة الراهنة التي تتعرض لها سورية ,والتي كان لها انعكاسات اقتصادية ومالية أثرت على عمل القطاع المصرفي بانتشار ظاهرة الديون المتعثرة التي تعتبر من المشكلات المصرفية ذات الأثر الجوهري على أداء المصارف, لما يترتب عليها من أعباء تشمل كل من العملاء المتعثرين والمصارف لذلك كان من الضروري الوقوف على نسب التعثر المالي ضمن عينة من المصارف التقليدية الخاصة العاملة في سورية والتي تشتمل على المصرف الدولي للتجارة والتمويل ,عودة ,سورية والمهجر , بيمو السعودي الفرنسي , بيبلوس , العربي خلال الفترة الممتدة من عام 2010 ولغاية العام 2016, ومعرفة نقاط الخلل والضعف ومحاولة إيجاد حلول لها بالشكل الذي يضمن استمرار المصرف ويحد من ظاهرة الديون المتعثرة ويخفف من آثارها السلبية. وتوصلت الدراسة للنتائج الآتية : عند التحقق من أسباب التعثر خلال الأزمة السورية نجد بأنها تعود لنوعي المخاطر المنتظمة وغير المنتظمة, أي جزء من هذه المخاطر يعود لسوء إدارة العملية الائتمانية في المصارف وعدم اتخاذ القرار الائتماني وفق أسس علمية ومدروسة, وجزء منه يعود لتداعيات الأزمة الراهنة وانعكاساتها على القطاع المصرفي,آخذين بعين الاعتبار أن نمو المحفظة الائتمانية يترافق مع نمو التسهيلات المتعثرة ما لم تتخذ إجراءات وتدابير تضمن بقاء نسب التعثر ضمن الحدود المسموح بها . كما أوصت الدراسة بضرورة إعادة هيكلة آلية منح الائتمان في المصارف السورية بما يتناسب مع متغيرات السوق السورية واتخاذ التدابير والإجراءات اللازمة للتحوط من مخاطر التعثر ومساعدة العملاء المتعثرين للحد من خسائر المصرف.